2019
DOI: 10.1515/cclm-2019-0471
|View full text |Cite
|
Sign up to set email alerts
|

Validation and standardization of the ETP-based activated protein C resistance test for the clinical investigation of steroid contraceptives in women: an unmet clinical and regulatory need

Abstract: BackgroundRegulatory bodies recommend the use of an assay based on the assessment of the endogenous thrombin potential (ETP) for the investigation of the activated protein C resistance (APCr) in the development of steroid contraceptives in women. However, the assays described in the literature are home-made and not standardized regarding the method, the reagents, the reference plasma and the quality controls. In the absence of any commercially available method, we aimed at validating the ETP-based APCr assay.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
67
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 34 publications
(71 citation statements)
references
References 28 publications
4
67
0
Order By: Relevance
“…Our previous study showed that a validated methodology of ETP‐based APC resistance assay enables batch‐to‐batch management while maintaining the sensitivity, specificity, and robustness over a batch change . Based on 86 measurements (38 for batch 202685 and 48 for batch 202947), the ETP ratio did not show a significant difference between the 2 batches used.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Our previous study showed that a validated methodology of ETP‐based APC resistance assay enables batch‐to‐batch management while maintaining the sensitivity, specificity, and robustness over a batch change . Based on 86 measurements (38 for batch 202685 and 48 for batch 202947), the ETP ratio did not show a significant difference between the 2 batches used.…”
Section: Discussionmentioning
confidence: 97%
“…27,28 Hence, our group recently proposed a validated methodology that meets all the regulatory requirements in terms of analytical performances. 29 However, different units have been reported in the literature for the expression of the ETP-based APC resistance results. Among these different units, the so-called "normalized APC sensitivity ratio" (nAPCsr) is certainly the most popular.…”
Section: Backg Rou N Dmentioning
confidence: 99%
See 3 more Smart Citations